-(4x+5)=5(x+6)

Simple and best practice solution for -(4x+5)=5(x+6) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -(4x+5)=5(x+6) equation:



-(4x+5)=5(x+6)
We move all terms to the left:
-(4x+5)-(5(x+6))=0
We get rid of parentheses
-4x-(5(x+6))-5=0
We calculate terms in parentheses: -(5(x+6)), so:
5(x+6)
We multiply parentheses
5x+30
Back to the equation:
-(5x+30)
We get rid of parentheses
-4x-5x-30-5=0
We add all the numbers together, and all the variables
-9x-35=0
We move all terms containing x to the left, all other terms to the right
-9x=35
x=35/-9
x=-3+8/9

You can always share this solution

See similar equations:

| 10q=-40 | | 1.1x+1.6=2x+0.7 | | -3q+5=-1 | | 180=(12y) | | 11-n=4 | | 0.07x+0.6x=2x-5.53 | | w=45-4w | | f=62+34 | | n/5+16=21 | | 180=(4x+2) | | n/8-4=2 | | 3+3x-x+2=3x=4 | | n/6+59=61 | | -5(x+2)=-3x-6 | | 4(x+8)-8(4x-9)=18 | | X+3/2x-1=5 | | n/3+5=12 | | n/4-6=7 | | f=36=51 | | 7+6c/6=-3 | | 7+x=-85 | | n/2+9=20 | | 0.9x=0.04x-4.3 | | 3x(-2x(-2x)+4x-7)=0 | | n/7+11=13 | | 8(x+2)=-16 | | 39=d-3 | | 9-2x=5x=12 | | 3x(-2x^2+4x-7)=0 | | 4(x+9)-8(4x-9)=18 | | 3g?2g=15 | | -37.5=2.5+5r | | 6(x-3)+3x=5(x-2 | | (2p+3)(2p-3)(p+7)=0 | | 9x-9=3(3x+4) | | 6n-8=52 | | 80=9+x | | v/7-2=-8 | | v/7-4=7 | | 9x-8=-3x+4 | | 0.7n+0.2=0.4n+1.7 | | 3s+4=-5 | | 9x-(4+x)=2(-x-7) | | 7s-45=32 | | 98=4(1+2x)/(7X+1.09)x= | | 0.3(6x-5)=-1.5 | | 1/2*30-n=4 | | 12p+1=9p^2 | | 6x+9-9x+9=-3x+18 | | -7(2x+1)+10x=5 | | 6g+7=14+g | | -17+n=-9 | | 73+(x+-11)+x=180 | | x*1.6=5120 | | X^-4x=-1 | | 2x+22=164 | | 0.09x+x=6.5 | | -1(-4z+7)=9 | | 2j?3=5 | | 7q-2=11q | | 1=5-b | | 12=17-1w | | 8x-25=2x-12 | | 4(t+25=4(t+50)-4(0.15t) | | 2x-6;=9 |

Equations solver categories